The Effect of Digital Literacy and Technology Adaptation on the Performance Effectiveness of Cadres with Digital Competence as an Intervening Variable - Asep Kristiyanto; Imam Failasuf Fadil (Proceeding of The International Conference on Business and Economics, 2026)
Digital transformation in public health services requires cadres to possess adequate digital literacy and technology adaptation skills. This study aims to analyze the influence of digital literacy and technology adaptation on the effectiveness of cadre performance, with digital competence as an intervening variable in Pekalongan Regency. The study population was health cadres in Pekalongan Regency, with a sample of 90 respondents selected using a technique that was part of the total population of 285 respondents. Sampling used simple random sampling. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data analysis used [analytical methods, for example: Structural Equation Modeling (SEM) or Path Analysis] to examine direct and indirect relationships between variables. The research results are expected to provide an overview of: (1) the influence of digital literacy on the effectiveness of cadre performance, (2) the influence of technology adaptation on the effectiveness of cadre performance, (3) the influence of digital literacy on digital competence, (4) the influence of technology adaptation on digital competence, (5) the influence of digital competence on the effectiveness of cadre performance, and (6) the role of digital competence as an intervening variable in the relationship between digital literacy and technology adaptation on the effectiveness of cadre performance. The findings of this research are expected to serve as a basis for developing training programs and increasing the capacity of health cadres in the digital era, particularly in Pekalongan Regency.